TOEIC Smart Green book reading. (Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2012)
Lesson 1: Invitations; Lesson 2: E-mails; Lesson 3: Warnings/Cautions; Lesson 4: Weather Reports; Lesson 5: Guarantees; Lesson 6: Telephone Messages; Lesson 7: Articles; Lesson 8: Recipes; Achievement test; Answer Key.